Inhibition of the p38 MAPK pathway in human CD1c+ Dendritic Cells enhances their function for cancer immunotherapy - Kaur, Aanchal Preet (2021)
The success of immune checkpoint inhibitors (ICI) in treating chemo-radiotherapy resistant tumours like melanoma has ignited renewed interest in cancer immunotherapy. Despite the success of ICI, a substantial proportion of patients do not respond. The resistance mechanisms used by tumours to evade ICI-dependent effector mechanisms overlap with those used during the cancer immune-editing process. Furthermore, the severe cytotoxicity that occurs as a consequence of this, complicates the use of these therapies.